Effectiveness of Plyometric Training Methods on Increasing Lower Limb Muscle Power of Karate Athletes in Karawang - Nadiir Rizki Hermawan; Muhammad Fitrah Ramadhan; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Universitas Pendidikan Mandalika, 2026)
This study was motivated by the suboptimal lower limb muscle power of karate athletes in Karawang, which was assumed to result from the use of conventional and less varied training methods. Lower limb muscle power is a highly important component of physical fitness in supporting technical performance, particularly explosive movements such as kicks in kumite. An effective training method is therefore needed, one of which is plyometric training, widely recognized for improving explosive muscle performance. This study employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The sample consisted of 20 karate athletes. The instrument used was the vertical jump test to measure lower limb muscle power. Data were analyzed using a paired sample t-test after fulfilling the prerequisite tests of normality and homogeneity. The results showed a significant improvement in lower limb muscle power, indicated by an increase in the mean score from 45.30 cm to 52.75 cm, representing a 16.45% improvement. Hypothesis testing showed a significance value of p < 0.05, indicating a significant effect of plyometric training on lower limb muscle power enhancement. The discussion revealed that this improvement occurred due to neuromuscular adaptation through the stretch-shortening cycle mechanism, which increases muscle contraction efficiency and explosive force. It can be concluded that plyometric training methods are effective in improving lower limb muscle power of karate athletes in Karawang and are recommended as part of training programs.